The Use of Protein Modification and Ion Mobility-Mass Spectrometry to Probe Protein Structure - al-jabiry, asia (2022)
Mass spectrometry (MS) is considered to be indispensable technology for the use in modern pharmaceutical drug discovery and development processes. However, MS is rarely used as a screening technology for protein structure. In this project, ion mobility-mass spectrometry (IM-MS) methods are developed to investigate protein structure with the use of chemical modification and genetic modification. Collision induced unfolding (CIU) method was optimised for measuring the mobility of ubiquitin (Ub) drift traces and the collision cross section (CCS) was calculated. The mobility was measured in the trap by acquiring several voltages and monitoring the drift trace of the lower state ion ([M+6H]6+ and [M+5H]5+. By combining the CIU method and chemical modification of proteins we can enhance the understanding of protein structure in the gas phase. Acetylation was carried out first on ubiquitin, the results showed a difference in the drift trace for ubiquitin after acetylation. This led to inspection of the MS/MS spectrum of intact Ub. The b-ion, corresponding to fragmentation at lysine residue K6, showed this residue to have importance for the structural integrity of the protein. Therefore, different K6 mutant were obtained and their CIU were acquired. The results confirmed that the K6 reside is indeed crucial in the ubiquitin unfolding pathway. Acetylation of this residue, or its replacement with alanine (K6A Ub) produced a conformationally destabilised form of the protein, which unfolded at lower collision energies. Wild type Ub and its mutant K6O mutant shared the fact the K6 is present, and the result showed they have the same CIU unfolding profile, In contrast the NoK and K6R mutant where the K6 has been modified to R, resulted in a more stable compact structure as evidenced by the CIU profile. Diethylpyrocarbonate modification of the single the histidine residue in Ub, which was postulated to interact with K6 in the gas phase structure resulted in modest destabilisation of compact Ub, while succinylation of the N-terminus had no clear effect on stability of the protein structure. Studies of molecular dynamics and charge distribution support the experimental data by rationalising the importance of protonated K6 and H68 interaction in the gas-phase stabilization of the native folding of Ub. Finally, the ubiquitin associating domain UBA2 was destabilised by adding an acetyl group to the N-terminus of the protein. The observation was interpreted by the breaking of a key intramolecular interaction between the N-terminus and the glutamate residue E22. Moreover, the behavious of different in charge states showed the important of addition of charge on the structure of proteins.